2020
DOI: 10.1007/s42448-020-00052-8
|View full text |Cite
|
Sign up to set email alerts
|

What Is a Child-Appropriate Interview? Interaction Between Child Witnesses and Police Officers

Abstract: Over the past decades, researchers have recognized a need to develop more suitable forensic interview protocols to meet children’s right to receive improved and adapted communication. This study examines to what extent a relatively novel implementation of an investigative protocol conducted by highly trained Norwegian police investigators helps children (n = 33), 3–15 years of age, to report more detailed information from a criminal allegation than a previous protocol. Additionally, we investigated the bidirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…We do agree , however, with the authors on two issues. One important finding from the current study, which concurs with past Norwegian studies on child interviewing (e.g., Johnson et al, 2015; Melinder et al, 2020; Thoresen et al, 2009), is the limited use of broad open‐ended invitations. While other aspects have improved over time, such as the reliance on facilitators to improve communication, the issues related to open‐ended question are still at a status quo.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…We do agree , however, with the authors on two issues. One important finding from the current study, which concurs with past Norwegian studies on child interviewing (e.g., Johnson et al, 2015; Melinder et al, 2020; Thoresen et al, 2009), is the limited use of broad open‐ended invitations. While other aspects have improved over time, such as the reliance on facilitators to improve communication, the issues related to open‐ended question are still at a status quo.…”
Section: Introductionsupporting
confidence: 90%
“…We would also like to note that the analyses of forensic child interviewing have moved forward to examine more elaborate perspectives of the dynamics between the interviewer and the child by employing sequential analyses (e.g., Gilstrap & Ceci, 2005; Melinder & Gilstrap, 2009; Melinder, Magnusson, & Gilstrap, 2020). These analyses take into consideration the bi‐directional pattern within an interview and help researchers better understand the dynamic interplay between children and interviewers, which the authors stated as one of the aims of their study.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of forensic child interviewing have until recently focused on the type of question asked during the interview (Lamb, Hershkowitz, Orbach, & Esplin, 2008; Thoresen, Lønnum, Melinder, & Magnussen, 2009), or have manipulated isolated variables in the laboratory to study effects of suggestive questioning and social pressure (Ceci & Bruck, 1995), or studied unstructured interviews of mock cases (Melinder & Gilstrap, 2009). Despite the introduction of systematic guidelines and recommendations, many field studies reveal that professionals across countries still struggle in their interview practice (Hershkowitz, Horowitz, & Lamb, 2005; Johnson et al, 2015; Korkman, Santtila, & Sandnabba, 2006), although improvements have also been reported (Cederborg, Alm, Nises, & Lamb, 2013; Melinder, Magnusson, & Gilstrap, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, the substantial phase starts. A limited amount of research has shown that the interviewer's ability to control their own emotions and to maintain self‐control during the interview are associated with their ability to ask recommended questions (Melinder et al, 2010), which furthermore seems to affect the child's free recall positively (Melinder et al, 2020). Finally, the interviewer is supposed to close the interview session in a child‐sensitive and empathic manner.…”
Section: Introductionmentioning
confidence: 99%
“…Following the implementation of the SI model in Norway (October 2015), two field studies have examined the technique with varied results in terms of the question types used by forensic interviewers (Baugerud, Johnson, Hansen, Magnussen, & Lamb, 2020) and the dialogical communication patterns between child and interviewer (Melinder, Magnusson, & Gilstrap, 2020). However, no study has examined the effects of the SI in a controlled laboratory setting where children's response accuracy can be assessed.…”
mentioning
confidence: 99%